Das aulas avulsas ao Lyceu Provincial: as primeiras configurações do ensino secundário na Província da Parahyba do Norte - Ferronato, Cristiano de Jesus (2012)
This thesis discuss the secondary education transformations in Parahyba why not in Brazil in the period between the first initiatives of the Brazilian Imperial National State Organization trough the eve of the Republic. Translated into dates, these two descriptions correspond to two moments which commence, respectively, in 1836, with the creation of Parahyba do Norte Provincial Lyceu, and 1884, when this institution was transformed into Normal School. These dates are central in the Provincial Lyceu history, since they represent the birth, consolidation and the struggle undertaken by teachers, men of letters and public administrators to continue to exist as the main secondary education institution in the province. Our research points which, in the Northern Parahyba creation of its Provincial Lyceu and problems of the Regency period, was inserted in the process called imperial Pact, established between provincial elites with the central power, in particular, led by Liberals. The work was constructed, based on historical references, studies carried out by Dolhknikoff, Gouvêa and Haidar, and conceptual language taken from Bourdieu, about the "symbolic systems", in addition to the field and configuration concepts. The authors consulted for this study have pointed out the difficulties and the delay in installation of several colleges by the provinces of Brazil Empire, whose effective consolidation and regular functioning and chronology are diverse in every province, as they present specific emergencies and individuals, apart from the good intentions, which we believe were present among those who contributed to the production of legislation and all the more specific overall for this type of educational institution. In this sense, is unanimous, in Brazil, the notion that the creation of these institutions marked the beginning of a new time of Brazilian secondary school organization, which we are considering as a period of modernization of that level of education. For the fulfillment of our goals we use as the main documentary base: speeches of Presidents' reports addressed to the province Legislative Council; provincial laws, regulations, ordinances and decrees about the secondary statement; maps; statistical data; student lists; budgets, teachers and directors, among others that helped us in our historiographical operation. The documentation was crafted in the light of the interpretative and conceptual referential proposed by Bourdieu and Magalhães. We believe that by the peculiarities of the Institution here investigated and the results achieved, the work contributes to a first view of the history of secondary education in the Parahyba Province and history of Lyceum institutions in Brazil.